Inhibitory activity of in vitro plants from Drosera capillaris against Mycobacterium tuberculosis - Rodríguez, Ángel (2010)
The objective of the work was to demonstrate the inhibitory activity of in vitro plants of Drosera capillaris (Droseraceae) on Mycobacterium tuberculosis. The plants of D. capillaris were propagated in in vitro cultures from plantlets and mature leaves. It was used metanolic extract and gas chromatography to determinate secondary metabolites. Lowenstein-Jensen media, supplemented with 1.25; 2.5 y 5 mg/mL concentrations of cloroformic fraction obtain from metanolic crude extract, was used in the growth evaluation of five M. tuberculosis strains. The results indicated that plantlets of 3 – 5 cm up to, were obtained 10 – 12 months after in vitro culture. The naphtoquinone plumbagin was determinated by comparison with currently pattern retention, like as another hidrocarbonic compounds seem to long chain. M. tuberculosis growth was inhibited in 40 – 93.1% range, 2.5 and 5 mg/mL treatments, respectively. The minimum inhibitory concentration (MIC) y MIC90 was 1.25 mg/mL and 2.5 – 5 mg/mL, respectively. Was showed the antibacterial activity in metanolic extract of D. capillaris in vitro plants, probably by the action of the plumbagin and another secondary compounds found.